(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This paper shows the control of microgrids at isolated sites powered by hybrid wind and solar energy sources. The machine used for wind energy conversion is a double fed induction generator (DFIG) and the battery bank is connected to a common DC bus from them. Photovoltaic (PV) arrays are used to convert solar energy. Solar energy is consumed in a cost-effective manner with a DC-DC boost converter on DFIG’s common DC bus. The voltage and frequency are adjusted by the indirect vector control of the line-side converter with drooping characteristics. It changes the frequency reference based on the energy level of the battery, slowing the overcharging or discharging of the battery. This system can be operated without wind power. Control algorithms for wind and solar systems include maximum power point tracking (MPPT). This system is designed for fully automated operation, taking into account all the actual conditions of the system also has external power support to charge the battery without additional requirements. The simulation model of the system is developed in the MATLAB environment, and the simulation results are displayed under various conditions. wind or sun impermeable, unbalanced load is equally non-linear, low battery charge state. Finally, the prototype of the system is implemented using a 5kW photovoltaic array simulator and a 3.7kW wound rotor asynchronous machine to generate experimental results to validate the theoretical model and design.